Adapting workforce development programs in times of crises: a multi-case study of administrative leaders and faculty representing three community colleges - Donahue, Craig Alan (My University, 2025)
Disastrous events often cause crises that affect higher education institutions' operations, including workforce development (WD) and career education (CE) programs. Hurricanes, tornadoes, fires, earthquakes, floods, campus shootings, terrorist attacks, and the recent 2020 COVID-19 pandemic have all created crises requiring dramatic pedagogical and facility environmental shifts at educational institutions. Higher educational institutions working through crises without much advanced notice often require immediate organizational responses from leaders and other employees to ensure learning continues. At the same time, facilities must remain available for continued educational practices. Institutional responses in times of crises require administrative leadership and faculty to quickly alter regular operations for students to continue workforce development (WD) and career educational (CE) courses and programs. Transitioning from in-person, hands-on course training modalities and environments to being solely online or virtual often requires immediate pedagogical changes when disaster-causing crises arise. At times, these environmental changes to online and virtual learning settings do not adequately meet employer needs or include state or federal career education requirements, and these shifts can cause disruptions to students’ academic success plans. Many college leaders and faculty confronted with crises may be unprepared when responding to crisis-induced operational challenges. Institutions must minimize interruptions of WD and CE programs; therefore, administrative leaders and faculty may find training in some form of crisis management (CM) to significantly assist with continued student learning and higher education institutional success. This study explored community college administrative leaders' and faculty's decisions, actions, and practices, including what the leaders and faculty learned when they faced sudden disaster-causing occurrences. Occurrences that required immediate responses to maintain normal or near-normal operations while transitioning from in-person, hands-on WD and CE courses to other environments while meeting student, institutional, career-specific, and employer needs and requirements. This study addressed WD and CE programs adapting in times of crises, often transitioning from in-person, hands-on WD and CE courses to online or other modalities during and post-crisis. Institutional leaders' and faculty’s decisions and actions, through semi-structured interviews, including reviews of CM or emergency response (ER) documents, served as data analyzed. The study explored whether crisis management (CM) strategies, policies, procedures, and preparation training took place before and during disasters to alleviate the negative aspects caused by crises. Additionally, this study examined the environmental and pedagogical changes higher educational institutions implemented in WD and CE programs to minimize course interruptions during and post-crisis. Institutional leaders and faculty responses, along with the CM documents from community colleges serving various regions, were studied to account for different disaster-causing crises. Pearson and Clair’s (1998) Crisis Management served as this study’s theoretical framework, with Pearson and Mitroff’s (1993) Five Phases of Crisis Management serving as the conceptual framework. This study incorporated a qualitative multi-case approach involving semi-structured interviews with community college administrative leaders and faculty serving three community colleges in two different regional locations throughout the United States. These leaders and faculty members served as the participants in this study and offered information and personal experiences regarding crisis-management preparation plans, policies, decisions, actions, and what was learned. The data collected, analyzed, and reported in this study may be helpful to organizations and institutions considering reviewing and possibly implementing crisis-management plans and practices in the future to minimize interruptions of WD and CE program environments and pedagogical practices prior to and when disaster-causing crises arise.
Keywords: Adapting workforce development programs; Career education programs during crises; Community college leaders in times of crises; Community college faculty adapting curriculum; Workforce development and career education during crises; Best practices when teaching during and after crises